Customer Profiling Among Milk Tea Shops: A Marketing Mix Perspective - L. Mercado, Joanna Lynn; P. Cañete, Shaniah Jane; G. Tindoy, Lady Pearl; C. Vergara, Cindy (International Journal of Management and Education in Human Development, 2024)
The primary objective of this quantitative research was to use a descriptive analysis as it involved identifying and describing the Customers profiling among milk tea shops: a marketing mix perspective. This study utilized the “Basic Marketing”, by Jerome McCarthy in 1960 reported that the four P's of marketing, all of which had an impact on buyer decisions and feedback. Each P is related to and dependent on the others. The Ps were controllable variables that a business used to level a successful marketing strategy. The respondents of this study were 100 random milk tea shop customers around Davao City. In which, the respondents ranging from eighteen to twenty - seven, who participated in the survey, and product, price, place and promotion affect their buying behavior of milk tea. Furthermore, there is no significant disparity when respondents were categorized based on their highest educational attainment, income, and frequency of consuming the milk tea. The hypothesis was rejected on demographic profile in terms of age. It is recommended that business owners should test out numerous creamers, flavors, and sweeteners before starting their own business. Milk Tea Shop owners were encouraged to use innovative marketing and promotional strategies, such as buy one get one free, free add – on, and free delivery, to boost their social media presence, especially on Facebook and Instagram. Additionally, for milk tea businesses and shops to continuously improve and ensure customer satisfaction in promotion and marketing strategies, it is recommended that milk tea customers express feedback or flavor preferences. This is significant because every business should build a customer profile so that when a consumer has specific drink preferences, the business might create loyal and frequent customers.